CHARACTERISTICS OF THE MANIFESTATION AND EXHIBITION OF MUAY TAY ATHLETE’S STRESS RESISTANCE AND SELF-CONTROL BEHAVIOR - Stepanyan, Anahit; Nadoyan, Anna (Modern Psychology, 2024)
Abstract The article is dedicated to the modern developmental problems of sport psychology.Nowdays the life of individuals is related to stress and stress resistance, which are reflected in everyday life, including sports. Learning successful ways to deal with stress is extremely important for an athlete. Sport (sporting activity) is inherently stressful for elite and novice Thai boxers,both of them equally exposed to stress during training and competition and need appropriate psychological support[2;8]. Almost every Thai boxer is in a state of high or pronounced stress. At the same time, men and women are equally susceptible to stress during sports activities. Such athletes widely use several self-supporting behavior strategies during their activities to cope with stress moreover, most of them reach a high level of expressiveness. In the work, an attempt was made to reveal the characteristics of the manifestation of stress resistance and self-control behavior formation of Muay Thai athletes, to study the mutual relationship between stress resistance and self-control behavior and the characteristics of behavior formation and manifestation. An experimental study was organized to study the manifestation of stress resistance of athletes of the mentioned sport [1]. Observations, testing and data processing methods were used for the studies, as a result very important conclusions were made. Various manifestations of stress resistance and self-control behavior among Thai boxers were revealed in the studied groups. In athletes, a high tension was observed in the self-monitoring behavior of positive reappraisal and seeking social support. This can be said to characterize Thai boxers as individuals who are focused on the personal, philosophical, reinterpretation of the problematic situation and are included in the broader context of the individual’s self-development work. Perception of social support also indicates athletes’ focus on interaction with other people, their support, attention, advice, sympathy, and expectation of concrete effective help. The dominant self-control behavior stress behavioral strategies of athletes are distraction and social distraction from the problem. An indicator of the level of neuropsychological stability or stress resistance is negatively correlated with self-control behavior strategies of taking responsibility and planning for problem solving, as well as problem solving strategies.